A 90-day OECD TG 413 rat inhalation study with systems toxicology endpoints demonstrates reduced exposure effects of the aerosol from the carbon heated tobacco product version 1.2 (CHTP1.2) compared with cigarette smoke. I. Inhalation exposure, clinical pathology and histopathology. (June 2018) - Phillips, Blaine W.; Schlage, Walter K.; Titz, Bjoern; Kogel, Ulrike; Sciuscio, Davide; Martin, Florian; Leroy, Patrice; Vuillaume, Gregory; Krishnan, Subash; Lee, Tom; Veljkovic, Emilija; Elamin, Ashraf; et al.
Abstract: Within the framework of a systems toxicology approach, the inhalation toxicity of aerosol from a novel tobacco-heating potentially modified risk tobacco product (MRTP), the carbon-heated tobacco product (CHTP) 1.2, was characterized and compared with that of mainstream smoke (CS) from the 3R4F reference cigarette in a 90-day nose-only rat inhalation study in general accordance with OECD TG 413. CHTP1.2 is a heat-not-burn product using a carbon heat source to produce an aerosol that contains nicotine and tobacco flavor. At equal or twice the nicotine concentration in the test atmospheres, inhalation of CHTP1.2 aerosol led to a significantly lower exposure to harmful constituents and induced less respiratory tract irritation, systemic, and pathological effects compared with CS. Nasal epithelial changes were less pronounced in the CHTP1.2- than in the CS-exposed groups and reverted in the nicotine concentration-matched group after a recovery period. Lung inflammation was minimal in the CHTP1.2-treated groups compared with the moderate extent seen in the 3R4F groups. Many other toxicological endpoints evaluated did not show CHTP1.2 aerosol exposure-related effects, and no effects not seen for 3R4F were observed. These observations were consistent with findings from previous studies in which rats were exposed to MRTP aerosols containing similar nicotine concentrations. Highlights: Potential modified risk tobacco product (CHTP1.2) aerosol contains less harmful constituents than cigarette smoke (CS). Lower uptake of harmful constituents from inhaled CHTP1.2 aerosol than from CS at comparable nicotine level. Upper airway effects of CHTP1.2 aerosol less severe and fully reversible in contrast to CS effects. Minimal lung inflammation effects of CHTP1.2 aerosol compared to moderate inflammation caused by CS. Similar weak systemic effects of CHTP1.2 aerosol and CS attributable to tube restraint stress and nicotine content.